Prelivanje znanja iz tujih podružnic v domača podjetja - Rojec, Matija (Naše gospodarstvo, 2006)
In spite of a clear theoretical conceptualisation of FDI spillovers, empirical literature provides mixed results. While case studies and sectoral analysis mostly speak in favour of positive spillovers, the prevailing individual panel data based analyses are more pessimistic. However, differentiation between vertical and horizontal FDI spillovers, the use of the Olley-Pakes estimation method, and other recent improvements have considerably improved the estimate of FDI spillovers based on individual panel data. One can expect that these and other improvements in empirical analysis will result in more positive estimates of FDI spillovers in future.
Keywords: podjetja; knowledge; znanje; upravljanje znanja; tuje investicije; direktne investicije; razvojna strategija